Pendidikan Lingkungan dan Taman Nasional: Strategi Konservasi Dunia dan Kegiatan Interpretasi Alam - Daniel H Henning; Ani Pakpahan (Department of Forest Resources Conservation and Ecotourism - IPB University, 1991)
This paper deals with environnlental education aspects of National Parks in ternts of the World Consen ationS tmtegy (W CS), values, and nahlralist interpretive activities.National Parks can provide the